4D light sheet imaging, computational reconstruction, and cell tracking in mouse embryos - Martin H. Dominguez; Jonathon M. Muncie-Vasic; Benoit G. Bruneau (STAR Protocols)
Summary: As light sheet fluorescence microscopy (LSFM) becomes widely available, reconstruction of time-lapse imaging will further our understanding of complex biological processes at cellular resolution. Here, we present a comprehensive workflow for in toto capture, processing, and analysis of multi-view LSFM experiments using the ex vivo mouse embryo as a model system of development. Our protocol describes imaging on a commercial LSFM instrument followed by computational analysis in discrete segments, using open-source software. Quantification of migration and morphodynamics is included.For complete details on the use and execution of this protocol, please refer to Dominguez et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.